1979
DOI: 10.2134/agronj1979.00021962007100020022x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Balance in Urine‐affected Areas of a New Zealand Pasture1

Abstract: The high rates of urine‐N deposited during grazing offers the potential for considerable N loss through volatilization, leaching, and denitrification. A field experiment was conducted to evaluate the magnitude and pathways of N transformations and losses under warm, moist conditions. Urine was applied to 3‐m2 plots in a ryegrass (Lolium perenne L.)‐white clover (Trifolium repens L.) pasture at 300 or 600 kg N/ha. These rates simulate the urine affected area of sheep and cattle, respectively. Ammonia volatiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 11 publications
5
74
0
1
Order By: Relevance
“…grazed' was identical to that of the 'mean urine ? grazed since 2003' patches (Ball et al 1979). In intensive dairy farming, urine affecting 40% of the pasture area has been estimated to decrease N fixation by at least 10% annually (Ledgard et al 1982).…”
Section: Balance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…grazed' was identical to that of the 'mean urine ? grazed since 2003' patches (Ball et al 1979). In intensive dairy farming, urine affecting 40% of the pasture area has been estimated to decrease N fixation by at least 10% annually (Ledgard et al 1982).…”
Section: Balance Resultsmentioning
confidence: 99%
“…Ball et al 1979;van Beek et al 2003). Where N inputs exceed N outputs, surpluses are assumed to result in N accumulation in the soil and/or in increased N transfer to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that grazing could cause considerable N loss under warm and moist conditions through leaching and denitrification (Ball et al 1979). However, grazing reallocates N between aboveground and belowground ecosystems, which could compensate soil N loss.…”
Section: Discussionmentioning
confidence: 99%
“…In intensively grazed dairy pasture systems, although the amount of NO3--N leached is affected by inputs of N fertilisers and organic waste effluents (Scholefield et al 1993;Di et al 1998aDi et al ,b, 1999Ledgard et al 1999a;Silva et al 1999;Monaghan et al 2000), the largest contribution comes from the N returned from the animal urine (Ball et al 1979;Ryden et al 1984;Field et al 1985;Silva et al 1999;Di & Cameron 2000, 2002b. In a grazed pasture, between 60-90% of the N ingested by the grazing animal is returned to the pasture in the urine and dung and more than 70% of the N returned is in the urine (Haynes & Williams 1993;Jarvis et al 1995).…”
Section: Introductionmentioning
confidence: 99%